Data Communications and Networks - Godbole, Achyut S., author 438955; Kahate, Atul, author 208567 (New Delhi : Tata Mcgraw Hill Education, 2011)
This book fulfills the need for a basic comprehensive text on data communications andnetworks. This second edition lays emphasis on key topics such as data transmission,transmission media, data compression, security, network types and topologies, Internetand TCP/IP protocol suite.